Hepatitis C‐positive Black patients develop hepatocellular carcinoma at earlier stages of liver disease and present with a more aggressive phenotype. Issue 9 (25th February 2021) - Shaltiel, Tali; Zheng, Serena; Siderides, Cleo; Gleeson, Elizabeth M.; Carr, Jacquelyn; Pletcher, Eric R.; Cohen, Noah A.; Golas, Benjamin J.; Magge, Deepa R.; Labow, Daniel M.; Branch, Andrea D.; Sarpel, Umut
Abstract : Background: In the United States, mortality after a diagnosis of hepatocellular carcinoma (HCC) is higher in patients who are Black than in patients of other racial groups. The objective of this study was to clarify factors contributing to this disparity by analyzing liver and tumor characteristics in patients with HCC who have a history of hepatitis C virus (HCV) infection. Methods: Records of patients with HCV and HCC at the authors' institution from 2003 to 2018 were retrospectively reviewed. Race and ethnicity were self‐identified. Imaging, laboratory, and pathologic features were compared between Black and non‐Black cohorts. Results: Among 1195 individuals with HCC, 390 identified as Black. At the time of HCC diagnosis, Black patients had better liver function, as measured by Child‐Pugh score, Model of End‐Stage Liver Disease score, histology of nontumor tissue, and fibrosis‐4 (FIB‐4) score (all P < .05). FIB‐4 scores were <3.25 in 31% of Black patients. In addition, Black patients had less early stage HCC (20.2% vs 32.3%; P < .05), larger tumors (median [interquartile range]: 3.5 cm [2.2‐6.2 cm] vs 3.1 cm [2.1‐5.1 cm]; P < .01), more multiple tumors (median, [interquartile range]: 1 tumor [1‐3 tumors] vs 1 tumor [1‐2 tumors]; P = .03), more poorly differentiated tumors (30.3% vs 20.5%; P < .05), and more microvascular invasion (67.2% vs 56.5%; P < .05). Conclusions: Black patients with HCV exposure develop HCC at earlier stages of liver disease than members of other racial groups. Nearly one‐third would not qualify for HCC screening using the common FIB‐4 cirrhosis threshold. Practice guidelines that stress HCC surveillance for cirrhotic patients with HCV may need to be revised to be more inclusive for Black patients. In addition, tumors in Black patients carry worse prognostic features, and molecular studies are needed to characterize their biologic properties. Abstract : Results from this study reveal that hepatocellular carcinoma has a unique profile in Black patients who have hepatitis C virus exposure as the underlying liver disease. This hepatocellular carcinoma profile has 2 important features: lower fibrosis stage in the surrounding liver and more aggressive tumors.